The pathogenesis, diagnosis, prevention, and treatment of CAR-T cell therapy-related adverse reactions - Li, Yanping; Ming, Yue; Fu, Ruoqiu; Li, Chen; Wu, Yuanlin; Jiang, Tingting; Li, Ziwei; Ni, Rui; Li, Li; Su, Hui; Liu, Yao (Frontiers in Pharmacology, 2022)
Chimeric antigen receptor (CAR)-T cell therapy is effective in the treatment of refractory/relapsed (r/r) hematological malignancies (r/r B-cell lymphoblastic leukemia, B-cell lymphoma and, multiple myeloma). In addition, it is being explored as a treatment option for solid tumors. As of March 31, 2022, seven CAR-T therapies for hematological malignancies have been approved worldwide. Although CAR-T therapy is an effective treatment for many malignancies, it also causes adverse effects. The incidence of cytokine release syndrome (CRS), the most common adverse reaction after infusion of CAR-T cells, is as high as 93%.CRS, is the leading risk factor of immune effector cell-associated neurotoxicity syndrome (ICANS), as well as cardiovascular, hematological, hepatorenal, skin, pulmonary, and gastrointestinal toxicity. Severe adverse reactions complicated by CRS severely impede the widespread application of CAR-T therapy. The CAR-T product was initially approved in 2017; however, only limited studies have investigated the adverse reactions owing to CAR-T therapy compared to that of clinically approved drugs. Thus, we aimed to elucidate the mechanisms, risk factors, diagnostic criteria, and treatment of toxicities concurrent with CRS, thereby providing a valuable reference for the safe, effective, and widespread application of CAR-T therapy.